Effect of Vitamin C on Lead‐Induced Cell Viability Levels, Oxidative Stress, and Immune‐Related Gene Expression in Grass Carp Kidney Cells. (6th June 2021) - Liu, Jia; Zhang, Peijun; Gao, Chunshan; Yin, Yuwei; Wang, Nan; Li, Yuehong
Abstract: The aim of this study was to explore the effects of the potential of vitamin C in relieving lead‐induced antioxidant and immune responses in Grass Carp Ctenopharyngodon idella kidney (CIK) cells. In this study, CIK cells were treated with vitamin C (0, 60, 80, 100, 120, and 140 µM) and lead (0 and 25 µM). Cell viability, oxidative response, and immune‐related gene expression were assessed. These results showed that cell viability was significantly decreased by exposure to lead and that vitamin C supplementation alone had no significant effect on cell viability, but vitamin C supplementation can alleviate the effect of lead on cell viability. Furthermore, vitamin C supplementation can increase the antioxidant capacity and the expression of immune‐related genes. Ultimately, these results suggest that vitamin C has a protective effect on CIK cells when they are exposed to lead.